2018
DOI: 10.1016/j.ijfoodmicro.2018.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Sausage fermentation and starter cultures in the era of molecular biology methods

Abstract: Fermented sausages have a long tradition originating from Europe and they constitute a significant part of the Mediterranean diet. This kind of products has a specific microbiota that is typical of the region or area where they are produced. Therefore, in order to protect the traditional aspect of these products, it is essential to understand the microbial ecology during fermentation by studying the dynamic changes that occur and to select autochthonous starter cultures that can be used in the production. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 75 publications
(100 reference statements)
1
51
0
3
Order By: Relevance
“…The use of bacteriocinogenic cultures has been largely explored for fermented foods, including fermented meat products. In the case of fermented meat products, the bacteriocin producing strains used act as starter culture and contribute to the safety, by microbial competition, bacteriocin and lactic acid production and to the development of the desired organoleptic properties of the final product (7). In non-fermented meat products, bacteriocin producing lactic acid bacteria may be added as protective cultures and they are not expected to grow significantly or to produce large amounts of lactic acid.…”
Section: Monocytogenesmentioning
confidence: 99%
“…The use of bacteriocinogenic cultures has been largely explored for fermented foods, including fermented meat products. In the case of fermented meat products, the bacteriocin producing strains used act as starter culture and contribute to the safety, by microbial competition, bacteriocin and lactic acid production and to the development of the desired organoleptic properties of the final product (7). In non-fermented meat products, bacteriocin producing lactic acid bacteria may be added as protective cultures and they are not expected to grow significantly or to produce large amounts of lactic acid.…”
Section: Monocytogenesmentioning
confidence: 99%
“…High-throughput sequencing (HTS) techniques represent a relatively new approach in the way microbiologists address ecology and diversity in different environments, and consequently also in foods. As explained by Franciosa et al [25], in HTS, mixed nucleic acid molecules from a complex ecosystem can be sequenced, and therefore can lead to a detailed profile of the microbial populations (identified as operational taxonomic units, OTU) present. In the mid-2000s, HTS technologies became ubiquitous in microbial ecology studies, but limitations remain: a) DNA is a chemically stable molecule, which can be found for a long time after the death of a cell; b) quantification of the genera and/or species is only relatively possible.…”
mentioning
confidence: 99%
“…Actually, Vaz Velho et al (2013) used a higher initial concentration (9 log CFU/g) and, after 7 days, inoculated Listeria had decreased 2 log cycles. Alternatively, "Chouriço de Vinha d'Alhos" could have some endogenous bacteriocinogenic lactic acid bacteria, which may act in the same way as inoculated bacteriocinogenic lactic acid bacteria (Franciosa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%